Current treatment options and the role of peptides as potential therapeutic components for Middle East Respiratory Syndrome (MERS): A review - Sabeena Mustafa; Hanan Balkhy; Musa N. Gabere (Elsevier, 2018)
Middle East Respiratory Syndrome Coronavirus (MERS-CoV) is a highly pathogenic respiratory virus with mechanisms that may be driven by innate immune responses. Despite the effort of scientific studies related to this virus, Middle East Respiratory Syndrome (MERS) is still a public health concern. MERS-CoV infection has a high mortality rate, and to date, no therapeutic or vaccine has been discovered, that is effective in treating or preventing the disease. In this review, we summarize our understanding of the molecular and biological events of compounds acting as MERS-CoV inhibitors, the outcomes of existing therapeutic options and the various drugs undergoing clinical trials. Currently, several therapeutic options have been employed, such as convalescent plasma (CP), intravenous immunoglobulin (IVIG), monoclonal antibodies and repurposing of existing clinically approved drugs. However, these therapeutic options have drawbacks, thus the need for an alternative approach. The requirement for effective therapeutic treatment has brought the necessity for additional MERS treatments. We suggest that antimicrobial peptides (AMPs) may be used as alternative therapeutic agents against MERS-CoV infection. In addition, we propose the feasibility of developing effective agents by repurposing the existing and clinically approved anti-coronavirus and anti-viral peptide drugs. Keywords: MERS-CoV, Ribavirin, Interferon, Peptide therapeutics, Convalescent plasma, Intravenous immunoglobin, Antimicrobial peptides